The beneficial effects of virgin olive oil against oxidative stress induced by hypercholesterolemia in rats - Aicha Kribeche; Tayeb Idoui (Universidade Estadual de Maringá, 2022)
Cardiovascular disease (CVD) remains the major cause of mortality in the world, typically claiming a third of all deaths. The primary cause of CVD is atherosclerosis. Therefore, timely prevention and therapy of atherosclerosis are able to reduce the risk of the development of its clinical manifestations. Anti-atherosclerotic activity of medicinal plants mainly appears in their multiple effects. This study was carried out to evaluate the hypolipidemic activity of virgin olive oil in experimentally induced hyperlipemic Wistar. A total of 24 rats were randomly allocated to 4 equal groups and treated as follows for 50 days: (1) Normal control (NC); that were fed with a standart diet; (2) High Cholesterol Diet Control (HCD); which received high cholesterol diet for 50 days; (3) Animals receiving high cholesterol diet for 50 days, after this period the animals are fed for eight days by the standard food and receiving by gavage virgin olive oil (HCD+VOO) and (4) Animals fed for eight days with the standard food and receiving by gavage olive oil (VOO). High Cholesterol Diet containing yolk egg and coconut oil. Results showed that olive oil caused a significant (p < 0.01) reduction in serum levels of Total Cholesterol (TC), Triglycerides (TG), Low-Density Lipoprotein Cholesterol (LDL) and Atherogenic Index Serum (AIS). The results also demonstrated a significant (p < 0.01) increase in High-Density Lipoprotein Cholesterol (HDL). Moreover, virgin olive oil induced a significant reduction in liver lipid content. On the other hand, a High cholesterol diet induced oxidative stress was measured by estimating reduced glutathione level and amount of thiobarbituric acid reactive substances (TBARS) formed as an index of lipid peroxidation in a liver and a heart. Virgin olive oil supplementation attenuated all these variations. Our observations of the study indicate that the virgin olive oil has a significant antihyperlipidemic potential.